El Museo de La Plata en el avance del conocimiento geológico a fines del siglo XIX - Riccardi, Alberto Carlos (2008)
The contributions of the La Plata Museum to the geological knowledge of Argentina, began after this institution was founded in 1884, as an aftermath of the exploratory trips began by F.P. Moreno in 1873. The geological studies of the La Plata Museum, organized by Moreno, covered the Andean region between Puna and Tierra del Fuego, but with their main focus in the Patagonias Andes, took relevance from 1893 onwards when they became related to geographic explorations aimed at fixing the boundary between Argentina and Chile. As a result in about ten years the geographic and geological basis of extense and almost unknown regions were established. The study of the area between the Ultima Esperanza Inlet and lago Belgrano was mainly due to R. Hauthal, who defined its general stratigraphy and published the first geological map of the cordilleran region between c. 49° 30' and 52° S. The general geological scheme north of Lago Buenos Aires, to río Negro, was established by Santiago Roth. The stratigraphic succession, facies and structural changes through the argentine-chilean cordillera at the latitude of Lago Nahuel Huapi and Lago Lacar was studied by L. Wehrli, whilst at the latitude of Neuquén and Mendoza is mainly due to C. Burckhardt, with the contribution of R. Hauthal for the region between the Atuel and Diamante rivers. Important collections of Mesozoic and Cenozoic invertebrates, plants and vertebrates were made in these large areas, which were studied, respectively, by C. Burckhardt, F. Favre, W. Paulcke, O. Wilckens, F. Lahille y H. Ihering, by F. Kurtz, and by F. P. Moreno, A. Mercerat, A. S. Woodward, R. Lydekker and F. Ameghino.